Digital Leadership and Quality Culture in Islamic Educational Institutions: A Multi-Level Empirical Study - Wildan Saugi; Purwoko Purwoko; Azainil Azainil; Dwi Nugroho; Muhammad Ramli Buhari (Southeast Asian Journal of Islamic Education, 2025)
This study investigates the role of digital leadership in strengthening quality culture across Islamic educational institutions at various levels, from early childhood to higher education. Employing a qualitative multi-site case study approach, this research collected data through interviews, observations, and document analysis to explore how technological adoption and value-based practices shape institutional effectiveness. The findings reveal that digital leadership significantly enhances decision-making, coordination, instructional innovation, and the use of data-driven tools for quality monitoring. Leaders actively utilize digital platforms to support participatory, evidence-based governance and quality monitoring. The integration of Islamic values, including trustworthiness, discipline, and ethical digital conduct, further reinforces the consistency and depth of quality culture implementation, creating a leadership model that is both technologically adaptive and morally grounded. Higher education and senior secondary institutions show the highest level of maturity in integrating digital leadership with quality culture. In contrast, early childhood and elementary levels exhibit foundational digital adoption supported by strong value formation. The study concludes that successful digital transformation in Islamic education requires visionary leaders who can integrate technological competence, continuous quality improvement, and spiritual values. Practical implications highlight the need for structured digital capacity-building, leadership training, and strategic policy support. Future research is recommended to examine broader comparative contexts and the potential scalability of the proposed model.